PENJADWALAN FLOWSHOP DENGAN MIXED INTEGER PROGRAMMING UNTUK MEMINIMASI TOTAL FLOWTIME DAN TOTAL TARDINESS - Tantrika, Ceria Farela Mada (JEMIS (Journal of Engineering & Management in Industrial System), 2015)
Abstract Adi Bungsu (AB) Cigarette Company produces Clove Cigarette in four stages. Each stage is processed by one machine. Thus, the production line is described as flowshop. AB receive order from customer over country. Every month, AB should schedule the order from customer. Thus, AB should prioritize which order to be processed firstly. At this time, AB schedules their order by using First Come First Serve algorithm which prioritize the first order as the first processed job. Previously, this algorithm results in tardiness and high work-in-process. Therefore, this study aims to reduce the tardiness and work-in-process level. In this study, the scheduling problem is solved by using mixed integer programming. To minimize tardiness and work-in-process simultaneously, the objective include minimizing total tardiness and total flowtime. Meanwhile, this study also consider setup time separated from processing time so that setup can be done early while waiting job to be processed in previous stage. The results of this study show that mixed integer programming with two-criteria can be used to schedule job ordered by customer. In case of bicriteria scheduling problem with separated setup time, mixed integer programming generate better schedule than FCFS algorithm.